2020
DOI: 10.1101/2020.03.31.019216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus-host interactome and proteomic survey of PMBCs from COVID-19 patients reveal potential virulence factors influencing SARS-CoV-2 pathogenesis

Abstract: The ongoing coronavirus disease pandemic caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a global public health concern due to relatively easy person-to-person transmission and the current lack of effective antiviral therapy. However, the exact molecular mechanisms of SARS-CoV-2 pathogenesis remain largely unknown. We exploited an integrated proteomics approach to systematically investigate intra-viral and virus-host interactomes for the identification of unrealized SARS-CoV-2 host t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 32 publications
2
71
0
8
Order By: Relevance
“…Finally, we found upregulated ZAP70 (29), a tyrosine kinase that regulates motility, adhesion and cytokine expression of mature T-cells, as well as thymocyte development. A recent study found the SARS-CoV-2 nsp9 and nsp10 interact with NKRF (66), that inhibits IL-8 and IL-6 induction by competing with NF-КB for promoter binding. This interaction would lead to IL8/IL6 induction, and, among other, inhibition of ZAP70.…”
Section: The Interferon Signaling Is Activated In Dsmentioning
confidence: 99%
“…Finally, we found upregulated ZAP70 (29), a tyrosine kinase that regulates motility, adhesion and cytokine expression of mature T-cells, as well as thymocyte development. A recent study found the SARS-CoV-2 nsp9 and nsp10 interact with NKRF (66), that inhibits IL-8 and IL-6 induction by competing with NF-КB for promoter binding. This interaction would lead to IL8/IL6 induction, and, among other, inhibition of ZAP70.…”
Section: The Interferon Signaling Is Activated In Dsmentioning
confidence: 99%
“…With careful sample treatment, -omics can be very well used for diagnostic chips and to unravel to exact roles of individual substances within these cells, their metabolism, their transcription during cell division, or all of the above. Proteomics has been massively employed to elucidate the host interactions of SARS-CoV-2, the causative agent of COVID-19 [27][28][29][30][31][32], the greatest pandemic in our millennium.…”
Section: Proteomics Metabolomics Transcriptomics and Polyomicsmentioning
confidence: 99%
“…One very prominent aspect of microfluidic research is diagnostics on the single-cell or even molecular level. The significance of recent research towards microfluidics-based single cell diagnostic chips is apparent in health care, in our homes, and also very prominently in the fight against the COVID 19 pandemic: The diagnostic targets range from circulating tumor cells (CTC) [1][2][3][4][5][6], over parasites in blood [7][8][9][10][11][12][13][14][15], male fertility [16][17][18][19][20], molecular markers for infections [11,15,[21][22][23], cells of a specific stage in their life cycle [24,25], plant pathogens [26] and the SARS-CoV-2 proteome [27][28][29][30][31][32]. Depending on the exact target (either the entire cell or sub-cellular markers) there are different approaches to on-chip detection, each with their own underlying fundamentals and set of limitations.…”
Section: Introductionmentioning
confidence: 99%
“…But viral entry into the host cell is a prerequisite for this to happen. In the case of Covid-19, viral entry was shown to be mediated by the ACE2 receptor and the TMPRSS2 protease 27 Two recent studies capturing viral-host interactome tagged viral proteins as baits followed by affinity-purification and mass-spectrometry to identify a set of 332 (set 1: Gordon et al 16 ) and another set of 224 high confidence human proteins (set 2: Li et al 14 ) in HEK293 cell-lines which interact and co-precipitate with proteins of the Covid-19 (Supplementary Table 2). To test our hypothesis, we estimated the percentage expression of 553 host proteins (combined set of protein from both studies, Figure 4) that interact with viral proteins (a.k.a the viral interatome) across various cell-types in the different human tissues that may come in contact with the virus.…”
Section: Non-ace2 Expressing Cells Highly Express Proteins Found In Tmentioning
confidence: 99%
“…Further, researchers have used affinity-purification mass spectrometry to quantify the protein-protein interactions between viral proteins and human host proteins. These studies found 553 human host proteins in a human kidney cell line (HEK293) that suggest the mechanism of how Covid-19 invokes host inflammatory response 14 and identified potential drug targets for therapy 16 .…”
Section: Introductionmentioning
confidence: 99%